Characteristics of interdisciplinary research in author keywords appearing in Korean journals - Kwon, Sunyoung (Malaysian Journal of Library and Information Science, 2018)
Keywords for academic papers are terms selected and created by the authors, and are, in general, considered a core element that summarizes and represents the papers’ content. This research analysed the ways in which the author keywords for academic papers are used in multiple disciplines. The Brillouin index was used for an analysis of interdisciplinarity. As a result, 63.7 percent of the keywords were shown to appear in only one area of study. These cannot be considered keywords with interdisciplinarity, but rather with topic specificity. In addition, the interdisciplinarity degree of 80 percent of the keywords were low, between 0 and 0.499. This indicates that the majority of author keywords for academic papers do not show interdisciplinarity. Meanwhile, certain author keywords had a fairly high interdisciplinarity degree. In this case, they can be seen as topics that are researched in multiple disciplines. It was revealed that the interdisciplinarity degree of author keywords in art/physical education are lower than in the humanities or social sciences. This suggests that the interdisciplinarity of author keywords is lower in art/physical education than in the humanities or social sciences.